Ocular injuries from gel blasters: not just a harmless toy. Issue 6 (9th June 2019) - Hayes, Rylan; Dai, Shuan
Abstract : Gel blasters fire a hydrated gel polymer and are developed to circumvent the restrictions placed on paintball and airsoft guns. Because there are no reported cases of injury caused by gel blasters in the literature, some Australian jurisdictions have categorised them as a toy. Presented here are two cases of potentially blinding blunt ocular trauma which question the misguided notion they are a harmless toy. Two children each with a macrohyphaema were managed at a tertiary ophthalmology centre within 2 weeks of each other after being struck by a gel blaster projectile. Their vision ultimately returned to normal, but both face lifelong risks of ocular complications. These cases highlight the need for vigilance, and the appropriate restriction of powerful weapons, with the inherent need for eye protection when operating any such projectiles reiterated. It is recommended their licensing is made congruous with paintball guns to prevent false reassurance of their safety.